Appraising the role of reproductive health, family planning, maternal and child care in the context of population stablization in Africa (2000)
In a world of about 5.6 million people, growing by nearly 100million more every year, the future of the planet and especially the portin of it known as Africa, depends on promoting population stabilization. The roles reproductive health, family planning, maternal and child care can play in the achievement of thses population stabilization form the focus of this paper. Factors affecting population stabilization can be classified into two groups; namley background variables and intermediate or proximate variables. The former includes cultural, psychological, economic, social, health and environmental factors. The proximate determinants are those factors that have direct effect on population stabilization. The background factors operate through the proximate determinants to influence the stabilization of population since they do not have direct influence. This paper assesses the relative effect of four proximate determinants on population stabilization namely, reproductive health, family palnning, maternal care and child care, illustrating different effects of each factor.